Perceptions of sitting posture among members of the community, both with and without non-specific chronic low back pain - O'Sullivan, K.; O'Keeffe, M.; O'Sullivan, L.; O'Sullivan, Peter; Dankaerts, W. (2013)
Physiotherapists perceive upright, lordotic sitting postures to be important in the management of non-specific chronic low back pain (NSCLBP). Little is known about the perceptions of the wider community about seated posture, despite this being an important consideration before attempting to change seated posture. This study investigated perceptions of the best and worst sitting postures among members of the community, both with (n=120) and without (n=235) NSCLBP. Participants with NSCLBP perceived posture to be more important (p<0.001), and reported thinking about their posture significantly more frequently (p<0.001), than those without NSCLBP. 54% of participants selected a "neutral" lordotic sitting posture as their best posture, which was more frequent than any other posture (p<0.001). Sitting postures which were "straight", and were perceived to keep the head, neck and shoulders in good alignment were preferred. However, what people considered "straight" varied considerably. 78% selected a slumped sitting posture as their worst posture, which was more frequent than any other posture (p<0.001). The choice of best and worst sitting postures was not significantly influenced by gender, the presence of NSCLBP, or measures of pain, disability or back pain beliefs. Interestingly, a very upright sitting posture was the second most popular selection as both the best (19%) and worst (15%) posture. Overall, lordotic lumbar postures were strongly favoured among members of the community, which is broadly in line with the previously reported perceptions of physiotherapists. © 2013 Elsevier Ltd.